2021
DOI: 10.18488/journal.76.2021.82.76.95
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Methodology for Generating Bounded Solutions for the Set K-Covering and Set Variable K-Covering Problems: A Guide for or Practitioners

Abstract: As generalizations of the classic set covering problem (SCP), both the set K-covering problem (SKCP) and the set variable (K varies by constraint) K-covering problem (SVKCP) are easily shown to be NP-hard. Solution approaches in the literature for the SKCP typically provide no guarantees on solution quality. In this article, a simple methodology, called the simple sequential increasing tolerance (SSIT) matheuristic, that iteratively uses any general-purpose integer programming software (Gurobi and CPLEX in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…More benefits of SSIT are detailed in [19]. Successful applications of SSIT to solve several binary integer programs (BIP) have been documented in the literature [14][15][16][17][18][19]. For these applications, SSIT typically generates solutions guaranteed to be within 0.1% of the optimums in about 60 seconds on standard PCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More benefits of SSIT are detailed in [19]. Successful applications of SSIT to solve several binary integer programs (BIP) have been documented in the literature [14][15][16][17][18][19]. For these applications, SSIT typically generates solutions guaranteed to be within 0.1% of the optimums in about 60 seconds on standard PCs.…”
Section: Methodsmentioning
confidence: 99%
“…The pseudo code below summarizes the SSIT algorithm for a generic COP. More details about SSIT can be found in McNally et al [14]. SSIT Algorithm [ It is important to note that there is no need to "optimize" either the number of tolerances used or their values as well as the execution times for each tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…Successful applications of SSIT to solve several BIPs have been documented in the literature. McNally et al (2021) was able to solve 135 set K-covering problems (SKCP) from the literature on a standard PC in an average of 67 seconds and obtained an average guaranteed bound of 0.13% from the optimums using the Gurobi software package. Statistical analyses demonstrated that these SSIT results were as good as the best published results obtained from algorithms specifically designed to solve SKCPs.…”
Section: Multiple Pass Mode (Ssit Methodology)mentioning
confidence: 99%
“…The pseudocode and Fig. 1 (McNally et al., 2021) below summarize the SSIT methodology for a generic BIP.…”
Section: Overview Of the Simple Strategies For Solving Mmkps With Gurobimentioning
confidence: 99%
“…This approach involves splitting the application into separate microservices, each of which fulfills its own separate business purpose. For each microservice, there are the following characteristic requirements [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%